KEMELEKATAN HAK EKONOMI AHLI WARIS TERHADAP KARYA DARI PENCIPTA YANG TELAH MENINGGAL DUNIA: Legal Attachment of Economic Rights to Heirs in Relation to the Intellectual Works of Deceased Creators - Mayangsari, Fitria (Fakultas Hukum, Universitas Trisakti, 2025)
Upon the death of an individual, their legal rights and obligations do not extinguish but are transferred to their heirs in accordance with prevailing inheritance laws. In the Indonesian legal system, inheritance is governed by a pluralistic framework that incorporates both religious and civil law. Copyright, as an exclusive right granted to creators over their original works in the fields of art, literature, and science, is recognized as inheritable property. Despite its intangible nature, copyright possesses economic value and is therefore classified as part of the deceased’s estate. Conflicts often arise among heirs concerning the division and control of copyrighted works, particularly in sectors such as the music industry, which play a vital role in Indonesia's cultural and economic landscape. This study addresses two central research questions: (1) To what extent do economic rights remain attached to a creator’s work posthumously? and (2) What legal protections are afforded to heirs with respect to these economic rights? The findings reveal that economic rights associated with copyrighted works constitute intangible assets within the broader category of intellectual property. These rights are automatically transferred to the legal heirs upon the death of the creator, as stipulated by Indonesia’s Copyright Law (Law No. 28 of 2014) and relevant inheritance law, without necessitating any additional legal formalities. Consequently, copyright is legally recognized as a valid object of inheritance, enabling heirs to exploit, assign, or derive economic benefits from the work. Establishing clear and consistent legal frameworks for the inheritance of copyright is crucial in ensuring legal certainty and safeguarding the rights of heirs, thereby preventing potential disputes.